Avoiding slopping in top-blown BOS vessels - Brämming, Mats (Luleå tekniska universitet, Industriell miljö- och processteknik, 2010)
Slag formation plays a decisive role in all steelmaking processes. In top-blowing Basic Oxygen Steelmaking (BOS), i.e. in the LD process, an emulsion consisting of liquid slag, dispersed metal droplets and solid particles will, together with process gases, form an expanding foam. Extensive research has defined the parameters that govern the foaming characteristics of BOS slag emulsions. It is a well known fact that certain process conditions will lead to an excessive foam growth, forcing the foam out through the vessel opening (mouth). This process event is commonly known as slopping. Slopping results in loss of valuable metal, equipment damage, lost production time and pollution. A literature survey covering the slopping phenomena has been carried out, as well as a deeper investigation into the causes behind slopping on the BOS vessels, type LD/LBE, at SSAB EMEA Metallurgy Luleå, equipped with an automatic system for slopping registration using image analysis. Good slag formation and foam-growth control in order to avoid slopping is primarily accomplished by taking preventive "static" measures. Improved slopping control has been achieved by developing a new oxygen lance control scheme, featuring adjustment of the distance between the lance tip and the metal bath according to scrap quality and ore additions. If "static" measures cannot be effectuated, in-blow control measures are needed. For such "dynamic" measures to be effective, it is necessary to have a system for slopping prediction. In the early-1980s a system for foam level and slopping control, based on BOS vessel vibration, was temporarily installed and tested on one of the vessels in Luleå. Based on the experiences from these tests it was decided to re-investigate the vessel vibration measurement technique. Trials on industrial scale BOS vessels of type LD/LBE have been carried out. FFT spectrum analysis has been applied in order to find the frequency band with best correlation to an estimated foam height. The results show that there is a correlation ...